2006
DOI: 10.1534/genetics.106.059964
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Sterol Levels in Oxygen Sensing in Saccharomyces cerevisiae

Abstract: Upc2p and Ecm22p are a pair of transcription factors responsible for the basal and induced expression of genes encoding enzymes of ergosterol biosynthesis in yeast (ERG genes). Upc2p plays a second role as a regulator of hypoxically expressed genes. Both sterols and heme depend upon molecular oxygen for their synthesis, and thus the levels of both have the potential to act as indicators of the oxygen environment of cells. Hap1p is a heme-dependent transcription factor that both Upc2 and Ecm22p depend upon for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
138
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(144 citation statements)
references
References 47 publications
5
138
1
Order By: Relevance
“…Production of amorpha-4,11-diene and artemisinic acid were further increased by galactose-regulated (P GAL1 ) expression of the UPC2-1 transcription factor (13). UPC2-1 encodes an activated allele of UPC2 (17,18), which increases transcription of most ergosterol pathway biosynthetic genes and is also a regulator of hypoxia-expressed genes. We decided to reconstruct the production strain so that every mevalonate pathway enzyme as far as ERG20 is transcribed from high-expression galactose-regulated promoters (P GAL1 or P GAL10 ).…”
Section: Resultsmentioning
confidence: 99%
“…Production of amorpha-4,11-diene and artemisinic acid were further increased by galactose-regulated (P GAL1 ) expression of the UPC2-1 transcription factor (13). UPC2-1 encodes an activated allele of UPC2 (17,18), which increases transcription of most ergosterol pathway biosynthetic genes and is also a regulator of hypoxia-expressed genes. We decided to reconstruct the production strain so that every mevalonate pathway enzyme as far as ERG20 is transcribed from high-expression galactose-regulated promoters (P GAL1 or P GAL10 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, in response to low oxygen levels, Sre1 stimulates transcription of genes required for adaptation to hypoxia. In budding yeast, several transcription factors (Upc2, Ecm22, Mga2, Hap1, Rox1, 
) have been implicated in the response to sterol depletion and/or hypoxia, but none present significant sequence homology with members of the SREBP family (57,58,63,64). We have, therefore, investigated the effect of the deletion of TPA1 on genes controlled by Mga2 and Hap1 as representative of transcription factors affecting the response to oxygen concentration.…”
Section: Tpa1 Is Involved In Regulation Of Hap1 Transcription Factormentioning
confidence: 99%
“…In S. cerevisiae it has been observed that the cell senses oxygen availability through cellular heme and sterol levels (27)(28)(29). In C. albicans, no apparent homolog of ScHAP1 exists, but in recent studies a close ortholog of S. cerevisiae Upc2p and Ecm22p, both involved in sensing sterol depletion, has been identified.…”
Section: Oxygen Sensing In Candida Albicansmentioning
confidence: 99%